Endogenous Fe2+‐triggered self‐targeting nanomicelles for self‐amplifying intracellular oxidative stress - Zhongxiong Fan; Guoyu Xia; Qingluo Wang; Shiduan Chen; Jianmin Li; Zhenqing Hou; Ziwen Jiang; Juan Feng (Animal Models and Experimental Medicine)
Abstract Background Artesunate (ASA) acts as an •O₂− source through the breakdown of endoperoxide bridges catalyzed by Fe2+, yet its efficacy in ASA‐based nanodrugs is limited by poor intracellular delivery. Methods ASA–hyaluronic acid (HA) conjugates were formed from hydrophobic ASA and hydrophilic HA by an esterification reaction first, and then self‐targeting nanomicelles (NM) were developed using the fact that the amphiphilic conjugates of ASA and HA are capable of self‐assembling in aqueous environments. Results These ASA–HA NMs utilize CD44 receptor‐mediated transcytosis to greatly enhance uptake by breast cancer cells. Subsequently, endogenous Fe2+ from the tumor catalyzes the released ASA to produce highly toxic •O₂− radicals to kill tumor cells, although sustained tumor growth inhibition can be achieved via in vivo experiments. Conclusions Self‐targeting NMs represent a promising strategy for enhancing ASA‐based treatments, leveraging clinically approved drugs to expedite drug development and clinical research in oncology.